Isolation and Characterization of Two Postsynaptic Neurotoxins From Indian Cobra (Naja Naja) Venom - Huynh, Tam M.; Silva, Anjana; Isbister, Geoffrey K.; Hodgson, Wayne C. (Frontiers in Pharmacology, 2022)
The Indian Cobra (Naja naja) is among the “Big Four” responsible for most of the snakebite envenoming cases in India. Although recent proteomic studies suggest the presence of postsynaptic neurotoxins in N. naja venom, little is known about the pharmacology of these toxins. We isolated and characterized α-Elapitoxin-Nn2a (α-EPTX-Nn2a; 7020 Da) and α-Elapitoxin-Nn3a (α-EPTX-Nn3a; 7807 Da), a short-chain and long-chain postsynaptic neurotoxin, respectively, which constitute 1 and 3% of N. naja venom. α-EPTX-Nn2a (100–300 nM) and α-EPTX-Nn3a (100–300 nM) both induced concentration-dependent inhibition of indirect twitches and abolished contractile responses of tissues to exogenous acetylcholine and carbachol, in the chick biventer cervicis nerve-muscle preparation. The prior incubation of tissues with Indian polyvalent antivenom (1 ml/0.6 mg) prevented the in vitro neurotoxic effects of α-EPTX-Nn2a (100 nM) and α-EPTX-Nn3a (100 nM). The addition of Indian polyvalent antivenom (1 ml/0.6 mg), at the t90 time point, could not reverse the in vitro neurotoxicity of α-EPTX-Nn2a (100 nM). The in vitro neurotoxicity of α-EPTX-Nn3a (100 nM) was partially reversed by the addition of Indian polyvalent antivenom (1 ml/0.6 mg), as well as repeated washing of the tissue. α-EPTX-Nn2a displayed non-competitive antagonism of concentration-response curves to carbachol, with a pA2 of 8.01. In contrast, α-EPTX-Nn3a showed reversible antagonism of concentration-response curves to carbachol, with a pA2 of 8.17. De novo sequencing of α-EPTX-Nn2a and α-EPTX-Nn3a showed a short-chain and long-chain postsynaptic neurotoxin, respectively, with 62 and 71 amino acids. The important observation made in this study is that antivenom can reverse the neurotoxicity of the clinically important long-chain neurotoxin, but not the short-chain neurotoxin, from N. naja venom.